The Effectiveness of SPMI in Improving Academic and Non-Academic Performance at Private Universities in Medan City - Rahmad Dani; Ayu Andira; Mardiah Hasanah Nasution; Zakia Fadila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Private Universities (PTS) in Medan City face major challenges in improving academic and non-academic quality sustainably. This study aims to evaluate the effectiveness of the Internal Quality Assurance System (SPMI) in supporting the improvement of the performance of both aspects. Using an associative quantitative approach, data were collected through questionnaires from 75 respondents consisting of leaders, lecturers and quality assurance staff at 15 selected PTS in Medan. The analysis was conducted using simple linear regression. The results showed that the effectiveness of SPMI had a positive and significant effect on academic and non-academic performance. The determination coefficient value of 55.6% for academic performance and 65.7% for non-academic performance showed a substantial contribution of SPMI in improving institutional performance. These findings indicate that SPMI which is implemented consistently and comprehensively can be a strategic tool in building a quality culture that has an impact on strengthening the quality of learning, student activities and overall institutional governance. Therefore, strengthening the implementation of SPMI in the PTS environment is a crucial step to realize superior and competitive higher education.